The effect of fumaric acid-sodium bicarbonate on the green tea effervescent granuleâs quality made by dry granulation - Lestari, Agatha Busi susiati; Trisusilawati, Maria Yuli (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Tea plant (CamelliaÂ sinensisÂ L.)Â had beenÂ knownÂ toÂ contains epigallocathecin gallate (EGCG) that can be used to maintain the healthy. In this research, the green tea wasÂ tried to be formulated in effervescent dosage form, withÂ theÂ focusÂ onÂ theÂ effectÂ amongÂ fumaricÂ acid,Â sodiumÂ bicarbonate,Â andÂ the interactionÂ betweenÂ fumaricÂ acidÂ andÂ sodiumÂ bicarbonateÂ onÂ theÂ greenÂ tea extractÂ effervescent granuleâsÂ physical properties, that made by dry granulation method.Â PhysicalÂ propertiesÂ ofÂ effervescentÂ granuleÂ thatÂ beenÂ studyÂ were moistureÂ content,Â flowÂ rate,Â disintegrationÂ time,Â andÂ pHÂ ofÂ theÂ solution.Â The result showed that sodium bicarbonate was dominant in determining pH, granule flowÂ rateÂ andÂ moistureÂ contentÂ ofÂ granule,Â whereasÂ fumaricÂ acidÂ dominantÂ in disintegration time of effervescent granule.Key words: green tea, fumaric acid, effervescent granule, dry granulation